Inconsistencies in Halal Certification Regulations and Cosmetic Notifications: A Legal Analysis from the Perspectives of Health Law and Consumer Protection - Yatini; Muna, Izzatul; Maharani Putri, Prima (Universitas Muhammadiyah Purwokerto, 2026)
Halal certification and cosmetic notification are two essential regulatory regimes within Indonesia's product supervision system. However, overlapping authority between the National Agency of Drug and Food Control (BPOM) and the Halal Product Assurance Organizing Agency (BPJPH) under the Ministry of Religious Affairs has led to regulatory disharmony, resulting in inefficient licensing procedures and legal uncertainty. This study examines the implications of regulatory fragmentation on consumer protection and the right to public health. Using a normative juridical approach and supported by the theories of legal certainty, health law, and consumer protection, the findings indicate that the dualism of the licensing system leads to high transaction costs, delays in product distribution, and a decline in consumer trust in the safety and halal status of products. From the perspective of health law, this disharmony contradicts the principle of the right to health as stipulated in Law No. 17 of 2023. This study proposes a digital-based integrated licensing model for halal certification and cosmetic notification through a single-window system, which may enhance regulatory oversight, improve bureaucratic efficiency, and strengthen consumer protection by ensuring both product safety and the fulfillment of religious values.